TRPV1 Supports Axogenic Enhanced Excitability in Response to Neurodegenerative Stress - Risner, Michael L.; McGrady, Nolan R.; Boal, Andrew M.; Pasini, Silvia; Calkins, David J. (Frontiers in Cellular Neuroscience, 2021)
Early progression in neurodegenerative disease involves challenges to homeostatic processes, including those controlling axonal excitability and dendritic organization. In glaucoma, the leading cause of irreversible blindness, stress from intraocular pressure (IOP) causes degeneration of retinal ganglion cells (RGC) and their axons which comprise the optic nerve. Previously, we discovered that early progression induces axogenic, voltage-gated enhanced excitability of RGCs, even as dendritic complexity in the retina reduces. Here we investigate a possible contribution of the transient receptor potential vanilloid type 1 (TRPV1) channel to enhanced excitability, given its role in modulating excitation in other neural systems. We find that genetic deletion of Trpv1 (Trpv1-/-) influences excitability differently for RGCs firing continuously to light onset (αON-Sustained) versus light offset (αOFF-Sustained). Deletion drives excitability in opposing directions so that Trpv1-/- RGC responses with elevated IOP equalize to that of wild-type RGCs without elevated IOP. Depolarizing current injections in the absence of light-driven presynaptic excitation to directly modulate voltage-gated channels mirrored these changes, while inhibiting voltage-gated sodium channels and isolating retinal excitatory postsynaptic currents abolished both the differences in light-driven activity between WT and Trpv1-/- RGCs and changes in response due to IOP elevation. Together, these results support a voltage-dependent, axogenic influence of Trpv1-/- with elevated IOP. Finally, Trpv1-/- slowed loss of dendritic complexity with elevated IOP, opposite its effect on axon degeneration, supporting the idea that axonal and dendritic degeneration follow distinctive programs even at the level of membrane excitability.